جينيالوجيا الأنساق الثقافية في الرواية الجزائرية المعاصرة وتمثلاتها على مستوى المضامين - رواية الليالي حبلى بالأقمار أنموذجا - كرباع, علي; ملاوي, محفوظ (جامعة الوادي - university of Eloued, 2022)
تهدف الدراسات الثقافية إلى مقاربة الثقافة، وبحث سماتها وأنظمتها، وتراتبياتها، والإشتغال على مواضع الخلل بين أنماطها وأشكالها الاجتماعية، والكشف عن عوامل وشروط تحول الخطاب فيها، سعيا إلى خلخلة آثار الهيمنة على موقع المهمش في البناء الاجتماعي. وهذه الورقة البحثية تحاول قراءة بعض تلك الأنساق قراءة مقارنة من أجل بحث فاعلية النسق في تكوين المنظومة الخطابية في الرواية الجزائرية المعاصرة، والكشف عن المضمرات النسقية، وجدل المراوحة بين المنطوق الجمالي والكامن الثقافي من خلال فعل الحفر. Cultural studies aims at approaching culture, examining its features, systems, and hierarchies, working on the imbalances between its patterns and social forms, and revealing the factors and conditions for the transformation of discourse in it, in an effort to unravel the effects of domination on the position of the marginalized in the social structure. This research paper attempts to read some of those patterns, a comparative reading, in order to examine the effectiveness of the pattern in the formation of the discursive system in the contemporary Algerian novel, and to reveal the systemic implications, and the controversy between the aesthetic utterance and the cultural potential through the act of digging.
The Genealogy of Cultural Forms in the Contemporary Algerian Novel and Its Representations at the Level of Contents - The Nights Pregnant with Moons Novel as a Model
مقال
Keywords: الأنساق الثقافية، الرواية الجزائرية، المضمر النسقي، الجينيالوجيا، الحفر الأركيولوجي.; cultural patterns, the Algerian novel, the systemic implied, genealogy, the drilling archaeological.